Development and integration of teaching skills a problem for the teacher educators - Yadav, M. S.
Micro-teaching as an approach to the development of instructional skills in student teaching programme is a welcome innovation. This has limitations when viewed from total perspective of teacher preparation. In order to implement this technique more effectively, it has been felt that the steps that are generally followed in the skill development through micro-teaching are to be supplemented by certain additional steps. These steps has been discussed in this paper with proposal for concrete activities that may help development of instructional skills as well as their integration.
Keywords: Student teaching; Teachers -- Training of